New large-scale constraints on a phenomenological spectrum - Amendola, Luca (Monthly notices of the Royal Astronomical Society, 1997)
I consider the constraints that large-scale clustering puts on a three-parameter phenomenological power spectrum. In particular, I exploit the trend of the average density in volume-limited surveys with the sample size when large-scale fluctuations are present. Applying the method to recent determinations of the correlation function in volume-limited samples, it is shown that, if luminosity biasing is not dominant, then a high galaxy power spectrum normalization (bias factor larger than 2.6) or a primordial slope n > 1 is necessary. In this case, reporting even a modest scaling of the correlation function would put strong constraints on the power spectrum. If on the contrary the luminosity biasing completely accounts for the observed scaling of the correlation function, then a low normalization (bias less than or equal to unity) or n < 1 is more likely.